Some Fixed Point Theorems for Prešić-Hardy-Rogers Type Contractions in Metric Spaces - Satish Shukla; Stojan Radenović; Slaviša Pantelić (Journal of Mathematics)
We introduce some generalizations of Prešić type contractions and establish some fixed point theorems for mappings satisfying Prešić-Hardy-Rogers type contractive conditions in metric spaces. Our results generalize and extend several known results in metric spaces. Some examples are included which illustrate the cases when new results can be applied while old ones cannot.